PEMBANGUNAN BERKELANJUTAN DI TENGAH GLOBALISASI: ADAKAH HARAPAN? - Jhamtani, Hira (Global: Jurnal Politik Internasional, 2002)
Following a decade after the Rio Summit 1992, two central questions are constantly on debate concerning the paradigm of development. Firstly, is there a significant change in the paradigm of development as an impact of the Rio Summit? Secondly, does the WSSD have the capacity on leading the world in the implementation of sustainable development? This article describes problems that occur post-Rio Summit 1992, gives analysis of results produced by the WSSD, and ponders on the prospects of sustainable development in the future.